Prognostic Value of NT-proBNP in Predicting Adverse In-hospital Outcomes among Patients of STEMI getting Thrombolytic therapy without Clinical Manifestation of Heart Failure (Cardiovascular Journal, 2017)
Background: Risk stratification is extremely important in ACS patients especially acute STEMI. We studied in-hospital outcomes of acute STEMI according to their NT-proBNP level as a new prognostic marker.Methods: This observational prospective study was conducted to evaluate the significance of raised plasma NT-proBNP level on in-hospital outcomes in patients with STEMI, without clinical manifestation of heart failure. A total 88 patients of STEMI were included in the study. Among them 10 Patients have normal levels of NT-proBNP (